Coming To Terms A Theory of Writing Assessment - Lynne, Patricia (University Press of Colorado, 2004)
In a provocative book-length essay, Patricia Lynne argues that most programmatic assessment of student writing in U.S. public and higher education is conceived in the terms of mid-20th century positivism. Since composition as a field had found its most compatible home in constructivism, she asks, why do compositionists import a conceptual frame for assessment that is incompatible with composition theory? By casting this as a clash of paradigms, Lynne is able to highlight the ways in which each theory can and cannot influence the shape of assessment within composition. She laments, as do many in composition, that the objectively oriented paradigm of educational assessment theory subjugates and discounts the very social constructionist principles that empower composition pedagogy. Further, Lynne criticizes recent practice for accommodating the big business of educational testing-especially for capitulating to the discourse of positivism embedded in terms like "validity" and "reliability." These terms and concepts, she argues, have little theoretical significance within composition studies, and their technical and philosophical import are downplayed by composition assessment scholars. There is a need, Lynne says, for terms of assessment that are native to composition. To open this needed discussion within the field, she analyzes cutting-edge assessment efforts, including the work of Broad and Haswell, and she advances a set of alternate terms for evaluating assessment practices, a set of terms grounded in constructivism and composition. Coming to Terms is ambitious and principled, and it takes a controversial stand on important issues. This strong new volume in assessment theory will be of serious interest to assessment specialists and their students, to composition theorists, and to those now mounting assessments in their own programs.